Prediction Equations for Body-fat Percentage in Indian Infants and Young Children Using Skinfold Thickness and Mid-arm Circumference (Journal of Health, Population and Nutrition, 2010)
The objective of the study was to develop prediction equations for fat-mass percentage in infants in Indiabased on skinfold thickness, mid-arm circumference, and age. Skinfold thicknesses and mid-arm circumferenceof 46 apparently-healthy infants (27 girls and 19 boys), aged 6-24 months, from among theurban poor attending a well baby clinic of a hospital in Kolkata were measured. Their body-fat percentagewas measured using the D2O dilution technique as the reference method. Equations for body-fat percentagewere developed using a stepwise forward regression model using skinfold thicknesses, mid-armcircumference, and age as independent variables, and the body-fat percentage was derived by D2O dilutionas the dependent variable. The new prediction equations are: body-fat percentage=-69.26+5.76×B-0.33×T2+5.40×M+0.01×A2 for girls and body-fat percentage=-8.75+3.73×B+2.57×S for boys, where B=bicepsskinfold thickness, T=triceps skinfold thickness, and S=suprailiac skinfold thickness all in mm, M=mid-armcircumference in cm, and A=age in month. Using the D2O dilution technique, the means (SD) of the calculatedbody-fat percentage were 17.11 (7.25) for girls and 16.93 (6.62) for boys and, using the new predictionequations, these were 17.11 (6.25) for girls and 16.93 (6.02) for boys. The mean of the differences ofpaired values in body-fat percentage was zero. The mean (SD) of the differences of paired values for body-fatpercentage derived by the D2O technique and the new equations, applied on an independent sample of 23infants (11 girls and 12 boys) were -0.93 (6.56) for girls and 1.14 (2.43) for boys; the 95% confidence limitsof the differences of paired values for body-fat percentage were -2.03 to +3.89 for girls and -0.26 to +2.54for boys. Given that the trajectories of growth during infancy and childhood are a major risk factor for agroup of diseases in adulthood, including coronary heart disease and diabetes, these predictive equationsshould be useful in field studies.Key words: Anthropometry; Body mass index; D2O dilution; Fat-mass; Infants; Mid-arm circumference; IndiaDOI: 10.3329/jhpn.v28i3.5548J HEALTH POPUL NUTR 2010 Jun;28(3):221-229